Innate immune mechanisms hijacked by leukemia-initiating stem cells for selective advantage and immune evasion in Ptpn11-associated JMML - Hong Zheng; Peng Zhao; Zhenya Tan; Wen-Mei Yu; Juwita Werner; Elliot Stieglitz; Christopher C. Porter; Shanmuganathan Chandrakasan; Daniel S. Wechsler; Simon Mendez-Ferrer; Cheng-Kui Qu (Cell Reports)
Summary: Juvenile myelomonocytic leukemia (JMML) originates from mutated hematopoietic stem cells. The mechanism by which mutant stem cells are sustained, leading to leukemia development, remains elusive. By comprehensively examining transcriptomic profiles, cell compositions, developmental trajectories, and cell-cell interactions across various stages of tumor cell development in a mouse model of Ptpn11 mutation-associated JMML, we find that Ptpn11E76K/+ mutant stem cells exhibit de novo activation of the myeloid transcriptional program and markedly increased expression of innate immunity-associated antimicrobial peptides and pro-inflammatory proteins, particularly S100a9 and S100a8. Biological experiments confirm that S100a9/S100a8 confer a selective advantage to mutant stem cells through autocrine effects and facilitate immune evasion by recruiting and promoting immune-suppressive myeloid-derived suppressor cells in the microenvironment. Importantly, pharmacological inhibition of S100a9/S100a8 signaling effectively impede leukemia development from Ptpn11E76K/+ mutant stem cells. These findings collectively suggest that JMML-initiating cells exploit innate immune and inflammatory mechanisms to establish clonal dominance.